Efektivitas Pembelajaran Bahasa Arab dengan Aplikasi Duolingo: Literature Review - Restriana, Aisyah; Hijriyah, Umi; Koderi, (Shaut al Arabiyyah, 2025)
This study aims to analyze the effectiveness of using the Duolingo application in Arabic language learning, particularly in improving students' skills compared to conventional methods. The main issues addressed are students' low motivation in learning Arabic and challenges in mastering grammar due to the limitations of traditional methods. With the advancement of digital technology, gamification-based learning applications like Duolingo offer an interactive and engaging approach. However, research on the effectiveness of this application in the context of Arabic language learning remains limited This study employs a quantitative approach by comparing students' learning outcomes, motivation, and engagement using Duolingo and conventional methods through tests and documentation. Previous studies have shown that digital technology in language learning can enhance effectiveness, flexibility, and interactivity by providing instant feedback and increasing student motivation. The findings of this study confirm that Duolingo can enhance students' motivation and learning outcomes, although challenges such as technological access gaps and user readiness persist. These findings contribute to more innovative Arabic language learning strategies and provide recommendations for educators to adopt technology more effectively in teaching.